Penyuluhan Manfaat Tanaman Obat dan Gerakan 5M Guna Mencegah Covid-19 kepada Masyarakat Desa Way Lunik Kecamatan Abung Selatan Kabupaten Lampung Utara - Ajeng Triana; Antomi Saregar; Tri Agus Fajardini (FOUNDAE (Foundation of Advanced Education), 2021)
This community service program in the form of counseling is intended so that people can grow medicinal plants at home or commonly called live pharmacies, because as we know that live pharmacy plants are one type of plant that is useful in human life as an alternative source of treatment and has many benefits. One of them is to be able to increase the body's immune system and be able to fight viruses that are harmful to the body, especially the corona virus which is currently infecting many people all over the world. With the pharmacy plants living at home, it will make it easier for people to get and process medicinal plants for their own consumption as an effort to prevent corona virus infection.